Impact of truncal vagotomy on complicated peptic ulcer after distal gastrectomy with reconstruction by jejunal pouch interposition - Reika Yamashita; Naoto Takahashi; Kazuto Tsuboi; Norio Mitsumori; Hideyuki Kashiwagi; Katsuhiko Yanaga (Surgical Case Reports)
Abstract Background We encountered a case of marginal ulcer in the jejunum after distal gastrectomy with jejunal pouch interposition. However, it has not been reported and not confirmed the treatment. We chose truncal vagotomy, considering reduced morbidity and postoperative complications. Case presentation A case was a 69-year-old woman who was admitted to our hospital with melena. She had received curative distal gastrectomy with a 15-cm jejunal pouch reconstruction for early gastric cancer. Marginal ulcer in the jejunal pouch was detected by upper gastrointestinal endoscopy. She was given medication; however, she repeated hospitalization for melena and abdominal pain. Therefore, we decided to perform surgery, and truncal vagotomy was performed. The patient’s postoperative course was uneventful and was discharged on the 22nd postoperative day. Symptoms such as abdominal pain and melena were improved after truncal vagotomy. Conclusion We presented a case with a complicated peptic ulcer after distal gastrectomy with reconstruction by jejunal pouch interposition, which was successfully treated by truncal vagotomy, a surgical acid-reducing procedure which does not require resection of remnant stomach.